Caprock characterization of Upper Jurassic organic-rich shales using acoustic properties, Norwegian Continental Shelf. (November 2020) - Hansen, Jørgen André; Mondol, Nazmul Haque; Tsikalas, Filippos; Faleide, Jan Inge
Abstract: Our analysis of a comprehensive well log database and complementary mineralogical and geochemical information indicates that the risk for Upper Jurassic shales on the Norwegian Continental Shelf (NCS) to permit severe leakage of hydrocarbons from the reservoir is generally low, even in the case of substantial uplift. The content of brittle minerals, organic content, and compaction are dominant factors that explain the observed discrepancies in acoustic properties of organic-rich caprock shales. In particular, variations in silt-clay content in clay-dominated shales are found to primarily influence sonic velocity and to correlate closely with gamma-ray where the uranium contribution is limited ("grey shales"). Changes in organic content exhibit a stronger density-component and are seen to counteract or mask the compaction effect on velocity and density in Kimmeridgian black shales. The Hekkingen, Draupne and Tau formations are distinctly different from the underlying grey shale formations in acoustic properties, despite that the latter group also contains significant amounts of organic matter. Based on the low permeability and high capillary sealing capacity of clay-dominated shales, we conclude that even for a silty seal, migration through the caprock matrix is highly unlikely. Furthermore, tectonic fracturing is an ineffective leakage mechanism when the seal is poorly consolidated/cemented prior to uplift. Brittleness, related to both mineralogical composition and consolidation, is consequently a crucial parameter for predicting seal integrity in exhumed basins. Our rock physics framework and interpretations relate this rather qualitative parameter to acoustic properties, and thus, to seismic data. Highlights: Framework for evaluating seal efficiency and composition from acoustic properties. Evidence of excellent seal quality in Upper Jurassic organic-rich shales (low risk). Demonstrate effects of organic content and mineralogical composition. Consolidation influences shale behavior and brittleness during uplift.